Answer:
(3,9)
Step-by-step explanation:
u=(1,3) and v=(2,6),
u+v = (1+2, 3+6)
=(3,9)
Using this equation, f(3) = 23.
In order to find the value of f(3), we need to take the f(x) equation and put 3 everywhere we see x. Then we follow the order of operations to solve. So, let's start with the original.
f(x) = 2x^2 + 5sqrt(x - 2)
Now place 3 in for each x.
f(3) = 2(3)^2 + 5sqrt(3 - 2)
Now square the 3.
f(3) = 2(9) + 5 sqrt(3 - 2)
Do the subtraction inside of the parenthesis.
f(3) = 2(9) + 5sqrt(1)
Take the square root
f(3) = 2(9) + 5(1)
Multiply.
f(3) = 18 + 5
And add.
f(3) = 23
Answer:
6
Step-by-step explanation:
4 times 8 = 32. 56 - 32 = 24. 24 divided by 4 = 6.
-3*10= -30 to the 4th power is 810,000
10 to the -3 power is -1000 * 2 is -2000
810,000 * -2000 = -1,620,000,000
Answer: 12x+36
Step-by-step explanation:
If you use distributive property, 12 x X is 12x and 12 x 3 is 36 so you get 12x+36